From control to drift - Claudio U. Ciborra (Oxford University Press, 2000)
This book presents six in-depth case studies of large corporations which offer a rich picture of the main issues involved in information infrastructure implementation and management. It provides interpretations and theories that are relevant both for researchers and practitioners